Analysis of Factors Influencing Consumer Purchasing Decisions at the Weekly MSME Market at the Pemuda Field, Kuta Cane, Southeast Aceh - Superizal, Superizal (International Journal of Economics (IJEC), 2025)
This study aims to analyze the factors influencing consumer purchasing decisions at the weekly MSME market at Pemuda Field, Kuta Cane, Southeast Aceh. The research focuses on four key variables: price, product quality, promotion, and location. A quantitative approach was employed, utilizing a survey method with data collected through questionnaires distributed to 100 purposively selected respondents. Multiple linear regression analysis was used to examine the relationships between these variables and purchasing decisions. The results revealed that price and product quality significantly impact consumer purchasing decisions, with product quality emerging as the most dominant factor. In contrast, promotion and location did not exhibit significant effects. The findings suggest that consumers prioritize affordability and high-quality products over promotional activities or market accessibility. The study highlights the dual role of Pemuda Field as both a sports facility and a market hub, which enhances transaction opportunities by attracting visitors who initially come for recreation. Recommendations for MSME actors include improving product quality through better materials and packaging, adopting competitive pricing strategies, and leveraging the unique synergy between sports and market activities to attract more customers. These insights provide valuable guidance for MSMEs in designing effective marketing strategies to enhance customer satisfaction and business growth.